HUBUNGAN KEBISINGAN DI BANDARA HALIM PERDANAKUSUMA JAKARTA TIMUR TERHADAP GANGGUAN NON- AUDITORI PERMUKIMAN PENDUDUK WILAYAH BUFFER - Magfira Adha Hernayati; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Noise is any sound that does not want to be heard and disturb the individual. This noise has an impact on health. Continually, Noise can cause non-auditori disturbances, such as communication, psychological, physiological problem and sleep disorder. The purpose of this research is to know the relation of noise at Halim Perdanakusuma airport to non-auditori impact of people in residental Buffer area. This research is an observational analytic research with cross sectional design. The sample of this research were 96 respondents and taken based cluster random sampling. Analysis on this research using Chi Square Test. The results show that there are 5 location that have a noise value> 75 WECPNL. The result of this reserch shows that there was related between perception of noise (p = 0.0001, OR = 1,9), age (p = 0,001, OR = 7,9), distance betwen house to airport (p = 0,003, OR = 7.9). Based on the analysis, it can be concluded that there is a relationship between Halim Perdanakusuma airport noise and residental area aroundthe airport. The airport are advised to cooperate with the local government to evaluate the impacts felt by the community and develop a noise control program.